'Conception Trauma' of Group Analysis in Serbia. (June 2014) - Mojović, Marina; Despotović, Tija; Satarić, Jelica
Traumas that occur at the very beginning or just before the creation of a professional field, seem to be inscribed into their own conception. Bringing such traumatic experience to awareness is usually much more troublesome than those which intrude later into a field. Finding ways to let their contents emerge from being stored in some proto-mental, unthinkable psycho-social areas—and translating them into thinkable forms in search of finding meaning and integration—is a developmental challenge for the field and its organizations. After a brief reminder of the socio-political turbulence in Serbia over the last two decades, we shall give some basic information about the establishment of group analysis in Serbia with examples of traumatic intrusions into those processes. We shall then skip from external issues into the internal space, sharing some illustrative dream contents from the 'GAS reflection group', and show how they were helpful in understanding the 'organizational conception trauma'.